1986
DOI: 10.1080/07391102.1986.10506341
|View full text |Cite
|
Sign up to set email alerts
|

A New Bithiazole Derivative with Intercalative Properties

Abstract: In the course of studies related to new molecules with intercalative properties, we have been led to design and synthesize a bithiazole derivative, namely the 2-phenyl-6-[2'-(4'-(ethoxy-carbonyl)thiazolyl)]thiazolo[3,2- b][1,2,4]triazole (PETT). Its interaction with calf thymus DNA was studied using thermal denaturation and viscometry. Our results set in evidence that PETT acts as an intercalator, giving delta Tm, elongation and unwinding of DNA comparable to the values obtained for daunorubicin. The discrepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The interpretation of the binding initially proposed, in which the bithiazole binds to DNA by a classical intercalation process with the two thiazole rings in complete overlap with base pairs (Murakami et al, 1976;Takeshita et al, 1978;Lin & Grollman, 1981;Fisher et al, 1985;Miller et al, 1985), appears now very unlikely but cannot bedefinitively excluded. For simple bithiazole compounds an intercalative binding model is demonstrated (Kuroda et al, 1982;Sakai et al, 1982;Riordan & Sakai, 1983, Houssin et al, 1986, but because of steric hindrance it is difficult, if not impossible, for the bleomycinmetal complex to intercalate its bithiazole moiety between DNA base pairs. Several other investigations have converged to propose a model in which only one thiazole ring would be partially intercalated (Glickson et al, 198 1;Booth et al, 1983;Gamcsik et al, 1990) or inserted at a bending point of the DNA helix (Hihichart et al, 1985b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The interpretation of the binding initially proposed, in which the bithiazole binds to DNA by a classical intercalation process with the two thiazole rings in complete overlap with base pairs (Murakami et al, 1976;Takeshita et al, 1978;Lin & Grollman, 1981;Fisher et al, 1985;Miller et al, 1985), appears now very unlikely but cannot bedefinitively excluded. For simple bithiazole compounds an intercalative binding model is demonstrated (Kuroda et al, 1982;Sakai et al, 1982;Riordan & Sakai, 1983, Houssin et al, 1986, but because of steric hindrance it is difficult, if not impossible, for the bleomycinmetal complex to intercalate its bithiazole moiety between DNA base pairs. Several other investigations have converged to propose a model in which only one thiazole ring would be partially intercalated (Glickson et al, 198 1;Booth et al, 1983;Gamcsik et al, 1990) or inserted at a bending point of the DNA helix (Hihichart et al, 1985b).…”
Section: Discussionmentioning
confidence: 96%
“…The syn conformation has been previously proposed (Sakai et al, 1981;Lin & Grollman, 1981) and was again suggested by a study on phototransformed bleomycins which indicated that nitrogens rather than sulfurs of the bithiazole group may participate in the sequence specificity of bleomycin (Kuwahara & Sugiura, 1988). However, bithiazolecontaining derivatives whose structures have been solved by X-ray crystallography all appear to exhibit the trans orientation of the two rings (Koyama et al, 1968;Kuroda et al, 1982;Houssin et al, 1986). The different molecular contacts represented in this putative model need to be checked, but this scheme suggests that a sequence-specific interaction between DNA and the bithiazole group has occurred.…”
Section: ! Ementioning
confidence: 93%